Conservative management of odontogenic keratocyst by marsupialization - Adel M Al-Juhni; Ahmad F Al-Omar; Hasan A Muaadi; Anwar Minwer Al-Anazi (Wolters Kluwer Medknow Publications, 2021)
Odontogenic keratocyst (OKC) is a locally aggressive intraosseous tumor of odontogenic origin, associated with syndromes such as nevoid basal cell carcinoma syndrome. Also known as Gorlin syndrome, it is an autosomal dominant inherited condition. The disease is characterized by multiple basal cell carcinomas of the skin, multiple keratocystic odontogenic tumors, rib anomalies, and palmar and plantar pits. This article reviews a 3-year follow-up case that we have reported in the Dental University Hospital OMFS clinic at King Saud University, Riyadh, Saudi Arabia. The patient was a 13-year-old female that has been diagnosed with Gorlin-Goltz syndrome in 2018. She had multiple radiolucent lesions, two mandibular OKC, and maxillary dentigerous cyst. The extensive left OKC was treated with marsupialization followed by enucleation. Optimal results with low recurrence rate have been shown after using the marsupialization followed by enucleation and curettage, which agree with the present case results. Unfortunately, there is no gold standard or concrete recommendations that emphasize particular treatment modality. Nevertheless, this approach is considered effective and less invasive in treating OKCs, reducing the lesion size by drainage and decompression up to 47% of the initial size, allowing the preservation of critical anatomical structures. Furthermore, marsupialization prior to enucleation is an appropriate approach in young patients because it is the least treatment modality that interferes with the developmental process of jaws.